Adoption of Modern Irrigation Techniques in Qubiaba and Al-Amra Regions ,Sirte - AL. Makhlof, Hassin .; Mohammed, Hassan A.; Emhammed, Muftah .A.; Abd alrahman, Hager AL. Abd alrahman (Journal of Pure & Applied Sciences, 2021)
Irrigation of agricultural lands accounted for 70% of the water used around the world and represents up to 95% of all water uses in developing countries. The objective of this research is to study farmers' adoption level of modern irrigation techniques and the agricultural activity with a field survey covered Qubiaba and Al-Amra regions in Sirte. Qubiaba located at West about 30 km distance, while Al-Amra is about 55 km to the east. The data was collected using a questionnaire, which involved information about farmers, cultivated crops and farm irrigation systems. The data was gathered and handled over a period of three months. The results showed that 51-year-old and above was the dominant age category among the farmers, which recorded 65% in Qubiaba and the same percentage recorded in Al-Amra but for young farmers. There is a variation in the level of education among the farmers, Al-Amra recorded the highest level of education, while the illiteracy rate among the farmers of Qubiaba recorded 40%. On the other hand, Qubiaba was the highest in agricultural experience. The crop composition included vegetables, field crops and trees (olive and fruit). Trees were achieved 60% of the area in Qubiaba, whereas vegetables obtained the highest percentage (55%) in Al-Amra. The cultivated area by each farmer was ≤5 or >5, but the most dominant is ≤5 among the farmers of the two sites. The methods of irrigation used are surface and drip or sprinkler irrigation. In Al-Amra the adoption measures of using modern irrigation techniques were higher than that in Qubiaba. The rate, degree, and intensity of adoption were 85%, 85% and 72.25%  in Al-Amra and 35%, 35% and 12.25% in Qubiaba, respectively. The results also showed that the farmers of both sites  apply fertilizers with varied levels, but a higher rate was found in Al-Amra. The survey also indicated that farmers in the first site depend  on permanent labours, while the second one farmers do not tend to use permanent labours, but family members participated in agricultural.